An Innovative Video Game for Learning History - Udara, B.G.A.; Ranaweera, R. (NSBM Green University, 2019)
In Sri Lankan Schools, most subjects are taught in very traditional ways without much use of technology. This has become very problematic with students especially for the history parts of the subjects. In consideration of western music subject, most students follow finds its history part harder than other parts of the subject according to the lecturer in charge of the subject in the National Institute of Education (NIE), Maharagama, Sri Lanka. NIE is expected a software solution to make this history part more interesting and easier to the students. We have created a video game using Unity game engine for teaching western music history to school children. This system makes learning fun and interesting and also as this application is a game, it makes great leisure time activity which makes students enjoy while learning. The game is created and tested for three platforms as Windows PC platform (Windows 10), Android mobile platform (version 4.4.2 and upwards) and Web platform (WebGL, does not support mobile browsers yet). This game is created in Role Playing Game (RPG) style and is intended to make learning history interesting and fun. The game has covered areas which covers western music local school curriculum and guidance was provided by aesthetic department of the RPG.
Keywords: Education; video gaming; Visual Studio 2017; C#; Unity game engine; Android; WebGL